Dynamics of Curricular Changes in Initial Inservice Education and Training of Indian Forest Service - Ray, P. N. (Indian Forester, 1996)
Education and training curriculum of Indira Gandhi National Forest Academy needed fundamental transformation to meet the growing complexities of job requirement of IFS. Recently such changes have been implemented with a fairly comprehensive sandwich pattern course with phased programme. Within the general imperatives envisaged in New National Forest Policy training needs were identified. Multidisciplinary approach was accepted in contrast to metadisciplinary principle. Deficiencies of inputs on social, economic, ecological and environmental issues, have heen removed. Subjects of less or no relevance to present day context are either assigned less emphasis or deleted. Several new subjects were included. Quantitative approaches received more thrust. Subjects are also reorganized dissolving disciplinary boundaries. The unique blend of education and training orientation in the programme was maintained. The revitalization was made dynamic with inbuilt flexibility providing for incorporating changes. Material improvements in instrudional strategy formed integral part of the programme. The new curriculum is expected to meet the current and future needs of the Service.